Three Pahlavi manuscripts in the Matenadaran - Kostikyan, Kristine; Mehdi Baghi, Mohammad (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
About 450 manuscripts containing the works of Persian rich culture, science, and history are preserved in the Arabic script collection of the Matenadaran. Many of these manuscripts contain fine works of Persian art and calligraphy. The Persian manuscripts of the Matenadaran evoke the strong historical ties between Iran and Armenia and reflect the interest of Armenians towards Persian history, science, literature, and art. Apart from these manuscripts, three handwritten works referring to the Pre-Islamic Iranian culture are kept in the Non-Armenian Manuscript Collection of the Matenadaran. These manuscripts were bequested to the Matenadaran in 1970 by Mihrdat Tiryakyan, a poet and translator of a portion of Firdawsi’s Shahnamah into Armenian. The latter gifted to the Matenadaran two Persian manuscripts as well, in 1963 and 1973. The study of these five manuscripts granted to Matenadaran by Mihrdat Tiryakyan show that they had been earlier in possession of his father Harutyun and were related to his life and works.